Thrombin Generation and Neutralization Test (TGNT) - a Simple, Practical, and Sensitive Assay for Plasma Heparin Quantitation - Stavridis, I C; Vorias, N I (Thrombosis and Haemostasis, 1978)
A simple, quantitative method for detection of small amounts of heparin in human plasma is described. This method is based on the activation of coagulation factor X to its enzymatic form (Xa), by a mixture of RVV platelet substitute (Esnouf and Williams 1962, Esnouf and Jobin 1967) in a plasma rendered fibrinogen free without affecting other clotting factores (Bell et al. 1968, Bell 1973), by Arvin (Ancrod).Activation of factor X, results in thrombin generation. Thrombin inactivation by its natural inhibitors depends on the time elapsed from the start-point of activation. The inactivation process is enhanced by heparin (Biggs et al. 1970, Blomback et al. 1963) and this enhancement depends on the quantity of heparin in the plasma.